Respuesta :

Answer: 12?????? i dont know what the question is saying bc ur took a picture of something too close maybe get the whole question?

Step-by-step explanation:

Part A

y varies directly with x, so we know that y = kx for some constant k. Why the letter 'c' isn't used as a constant, instead of k, I'm not entirely sure.

We're told that x = 0.5 and y = 36. Let's use those values to find k

y = kx

36 = k*0.5

36/0.5 = k

72 = k

k = 72

The equation y = kx updates to y = 72x

As a check, plug x = 0.5 in to get,

y = 72x

y = 72*0.5

y = 36

which helps show that we have the correct equation.

Answer: y = 72x

===============================================================

Part B

If y = 1/3, then,

y = 72x

1/3 = 72x

72x = 1/3

x = (1/3)*(1/72)

x = (1*1)/(3*72)

x = 1/216

Note how I multiplied both sides by 1/72, which is the same as dividing both sides by 72.

Answer:  x = 1/216